Public attitudes towards e-cigarette regulations and policies in Taiwan - Chin-Shui Shih; Jean-Francois Etter (SAGE Publishing, 2020)
Background: There are various approaches to e-cigarette regulation globally. In Taiwan, the term "e-cigarette" is not found in existing regulations, but health authorities apply explanatory notes derived from standing laws to e-cigarette. Taiwan health authority is in the process of regulative reform to include "e-cigarette" in standing tobacco law. Our objective was to investigate the public's attitudes towards potential policy options for e-cigarette regulations in Taiwan. Design and Methods: We conduct an anonymous online survey in the general public. A questionnaire in Mandarin was posted on the website Stop-tabac.ch between July and November 2017. Results: Participants (n=236) were mostly male, young, highly educated, employed, and smoked or had smoked cigarettes in the past. Half were e-cigarette users. Four measures banning e-cigarettes, labelling content and nicotine level and establishing a maximum-allowable nicotine level were supported by more than 70% of participants. Vaping status was strongly associated with support for most measures after controlling for other factors in multivariate models. Conclusion: We documented attitudes of a self-selected sample of the general public in Taiwan regarding e-cigarette regulations and policies. These results may be useful to design studies in more representative samples and to inform e-cigarette regulations, policies and education campaigns.